A STUDY ON WOMEN ENTREPRENEURSHIP IN INDIAN INDUSTRIAL SOCIETY (International Journal of Food and Nutritional Sciences, 2022)
Economic empowerment of women, including reduction of female poverty require programmes that focus on identifying, developing and promoting alternative approaches to increase women’s access to and control over the means of making a living on a sustainable and long term basis